The effects of leadership, motivation, and entrepreneurial competence on teacher performance of elementary school teachers in Cikande District - Subihawati, Yuli; Syamsudin, Asep; Ristanto, Wahyu; Sumarjo, Wahid; Alfarizi, Abdul Wahid (Institute of Computer Science (IOCS), 2026)
The influence of school principal leadership, principal motivation at work, and principal entrepreneurial skills on elementary school teacher performance in the Cikande District is the subject of this study. The method used was multiple linear regression analysis using a quantitative approach. The results of the study showed that all three elements, independently and in combination, had a good and considerable influence on teacher performance. Revealing an Adjusted R Square value of 0. 565, the multiple coefficient of determination (R²) reveals a 56% influence of the combined effect of the independent variables leadership, work motivation, and the principal'sentrepreneurial skill on the dependent variable (teacher performance) Effective school principal leadership can help create a pleasant work environment and advance professionalism among teachers. High work motivation from principal work motivation creates enthusiasm and role models that drive optimal teacher performance. Meanwhile, the principal’s entrepreneurial competence encourages innovation and creativity in managing education, which positively impacts improving teacher performance. These findings indicate that the synergy all three variables together can create a productive and quality teacher performance system.